The Students’ Challenges in Speaking English at MTs Al Washliyah Kolam - Mahdiah Apandi; Azhary Tambusai; Ahmad Laut Hasibuan (PT Inovasi Pratama Internasional, 2022)
One of the most important skills that students must learn in learning English as a Foreign Language (EFL) is speaking. By mastering speaking skills, students can express their ideas during the communication process to achieve their communication goals. To achieve the goal of communicating in English speaking, the teacher's role in providing stimulation or strategy is also very necessary. However, in reality, many students in Indonesia have studied English for years but still find it difficult to speak English. Not only that, it turns out that the teacher's does not have a good strategy used by the teacher in the class, which is very monotonous so that students are bored and cannot accept speaking material well. The study aims to investigate the students` challenges in speaking English to describe strategies used by the teacher to overcome the speaking problems. The method of this research is qualitative. The data collection techniques used in this study were observation, interview, and documentation. The results of the interview show that there are internal and external factors. However, internal problems are most influence for students’ speaking skill. Students who experience a high level of anxiety have a hard time developing their speech. Appropriate learning activities as the teacher’s strategies can help teacher to overcome students’ challenges in speaking English.